Viral-Vector-Delivered Anti-Angiogenic Therapies to the Eye - Sanna Koponen; Emmi Kokki; Kati Kinnunen; Seppo Ylä-Herttuala (MDPI AG, 2021)
Pathological vessel growth harms vision and may finally lead to vision loss. Anti-angiogenic gene therapy with viral vectors for ocular neovascularization has shown great promise in preclinical studies. Most of the studies have been conducted with different adeno-associated serotype vectors. In addition, adeno- and lentivirus vectors have been used. Therapy has been targeted towards blocking vascular endothelial growth factors or other pro-angiogenic factors. Clinical trials of intraocular gene therapy for neovascularization have shown the treatment to be safe without severe adverse events or systemic effects. Nevertheless, clinical studies have not proceeded further than Phase 2 trials.